2008
DOI: 10.1007/s00259-007-0680-2
|View full text |Cite
|
Sign up to set email alerts
|

Optimisation of protocol for low dose CT-derived attenuation correction in myocardial perfusion SPECT imaging

Abstract: Our results indicate that reliable attenuation maps (mu-maps) of the thorax can be obtained even with the use of very low tube current. In our study, radiation exposure in CT-based AC for myocardial perfusion SPECT was substantially lowered (60% reduction). This is of particular importance in high-risk patients who may have to undergo follow-up scans and in research studies on volunteers. The procedure introduced is relatively simple and can be transferred to other SPECT/CT devices, which allow adjustment of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 25 publications
1
11
0
4
Order By: Relevance
“…This finding concurs with a previous patient based study, where a 1mA attenuation map was acquired at rest and a 2.5mA attenuation map at stress; both image sets revealed abnormal findings at a rate of 9.7% [12]. The patient based study and our work both describe potential dose saving in the region of 60%.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…This finding concurs with a previous patient based study, where a 1mA attenuation map was acquired at rest and a 2.5mA attenuation map at stress; both image sets revealed abnormal findings at a rate of 9.7% [12]. The patient based study and our work both describe potential dose saving in the region of 60%.…”
Section: Discussionsupporting
confidence: 81%
“…In our (static) phantom study we did not set out to determine the effect of respiratory motion on lesion detection. Variation in respiratory motion can be great, both within subjects and between them [30,31] but previous work comparing 2.5mA attenuation maps at stress and 1mA attenuation maps at rest saw equal detection rates (9.7%) of abnormal findings [12]. In this work the authors do comment that the attenuation map, with a rotation time of 14 seconds was sampled over approximately 3 respiratory cycles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Koepfli et al (65) and a recent study with SPECT/CT confirmed these findings (66). However, a potential misalignment between emission and transmission data poses the risk of incomplete correction and thus artificial perfusion defects and requires careful quality control to avoid reconstruction artifacts.…”
Section: Use Of Ct For Attenuation Correctionmentioning
confidence: 83%
“…Using SPECT/CT hybrid systems increases the specificity of myocardial SPECT to 80-90% [9]. SPECT/CT studies have shown that low-dose CT acquisitions are also feasible for CTAC [25]. The main limitation of CTAC is misregistration between myocardial SPECT and CT attenuation maps due to respiratory and cardiac motion [24,26].…”
Section: Ctac For Myocardial Spect Attenuation Artifacts In Myocardiamentioning
confidence: 99%